1991
DOI: 10.2134/jeq1991.00472425002000030026x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorus in Eroded Sediment from Corn and Soybean Tillage Systems

Abstract: Runoff, soil loss and sediment bound total Kjeldahl nitrogen (TKN) and Bray P‐1 phosphorus (P) losses were measured corn (Zea mays L.) and soybean [Glycine max (L.)] tillage systems subjected to simulated rainfall. Runoff and soil loss were influenced by contouring and tillage treatment. After 60 min of simulated rainfall, there was little or no runoff or soil erosion from plots which had recently been ridge cultivated along the contour. Soil and nutrient losses from up‐and‐down slope ridge‐till plots were nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 9 publications
2
11
0
3
Order By: Relevance
“…These results are consistent with the results of other researchers: Burwel et al (1977), McIsaac et al (1991), Fleige and Horn (2000), Kisic et al (2002), Ali et al (2006), Malam Issa et al (2006) and Warrington et al (2009) reported higher content of OM, plant available nutrients and other chemicals in soil sediments. Gaynor and Findlay (1995) concluded that conservation tillage reduces average soil loss compared to conventional tillage.…”
Section: Resultssupporting
confidence: 93%
“…These results are consistent with the results of other researchers: Burwel et al (1977), McIsaac et al (1991), Fleige and Horn (2000), Kisic et al (2002), Ali et al (2006), Malam Issa et al (2006) and Warrington et al (2009) reported higher content of OM, plant available nutrients and other chemicals in soil sediments. Gaynor and Findlay (1995) concluded that conservation tillage reduces average soil loss compared to conventional tillage.…”
Section: Resultssupporting
confidence: 93%
“…The magnitude of a 2 and the type of regression in Eq. (4) were similar to those reported by McIsaac et al (1991), Gachene et al (1997) and Hargrave and Shaykewich (1997). Thus, loss of N by erosion could be reasonably estimated from knowledge of sediment loss alone.…”
Section: Prediction Of Enrichment Ratio and N Losssupporting
confidence: 85%
“…We calculated values of E R of N for a range of agricultural soils under different crops, cultivation and weather conditions using the data from Massey and Jackson (1952), Sharpley (1985), Rose and Dalal (1988), Palis et al (1990), McIsaac et al (1991), Catt et al (1994), Hansen and Nielsen (1995) and Sombatpanit et al (1995). The mean value of E R from these data was 1.86 (S.E.…”
Section: N Loss and Enrichment Ratio (E R )mentioning
confidence: 99%
“…Research by Mannering and Bertrand (1971), Burwel et al (1977), Luk (1979), Krisztian (1992), McIsaac et al (1991), Basic et al (1991), Le Bissonnais and Singer (1993), Edwards et al (1993), Soilleau et al (1994), Fleige and Horn (2000) and Lindstrom et al (2000) suggests that there is a higher content of available nutrients and other chemicals in erosional drift compared to the soil from which the erosional drift originates.…”
Section: Introductionmentioning
confidence: 99%